The Role of Human Resource Management on Employee Performance through Work-Life Balance - Maswarni; Nofiar (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores the human resource management strategy, focusing on the role of work-life balance in enhancing employee performance. The company’s moderate performance serves as the main context of the problem. Using a qualitative case study approach, data were collected through interviews, observations, and documentation. Findings show that implementing work-life balance through time flexibility, satisfaction balance, and involvement balance positively impacts employee motivation, loyalty, and commitment to work. A SWOT analysis places the company in the growth quadrant, highlighting its strengths and opportunities for further development. However, challenges remain, particularly regarding the absence of standard operating procedures and issues of discipline, which hinder optimal performance. The study concludes that work-life balance is a critical factor in improving employee performance and should be integrated into the company’s human resource strategy to achieve sustainable growth. Strengthening standard operating procedures and discipline policies is recommended to maximize the positive impact of work-life balance initiatives on performance outcomes.